Microstrip band-stop filter based on double negative metamaterial - Badr Nasiri; Ahmed Errkik; Jamal Zbitou (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In this work, we present a novel miniature band stop filter based on double negative metamaterial, this circuit is designed on a low-cost substrate FR-4 of relative permittivity 4.4 and low tangential losses 0.002. The proposed filter has a compact and miniature size of 15 mm in length and 12mm in width without the 50 Ω feed lines. The resonator was studied and analyzed with a view to achieving a band-stop behavior around its resonant frequency. The band-stop characteristics are obtained by implementing the metamaterial resonator on the final structure. The obtained results show that this microstrip filter achieves fractional bandwidth of 40% at 2 GHz. Furthermore, excellent transmission quality and good attenuation are achieved. This filter is an adequate solution for global system for mobile communications (GSM).